Extracellular proteins of Trichoderma guizhouense elicit an immune response in maize (Zea mays) plants - Xu, Yu; Zhang, Jian; Shao, Jiahui; Feng, Haichao; Zhang, Ruifu; Shen, Qirong (Plant and soil, 2020)
Aim Trichoderma guizhouense NJAU 4742 (Tgui) can serve as a promising strain for the development of novel biofertilizers and biofungicides. Plants primed with Tgui via inoculation were investigated to clarify the underlying mechanisms that promote root growth and development and activate the plant innate immune response. Methods The relative expression of defence-related genes and of genes involved in the auxin signalling pathway in Zea mays and Arabidopsis thaliana was quantified. Scanning electron microscopy (SEM) was performed to visualize the colonization of Tgui in maize roots, and a proteomic approach was used to identify Tgui-derived elicitors. Results The establishment of Tgui in the rhizosphere of maize leads to the stimulation of the auxin synthesis pathway in maize and subsequently leads to increased plant growth. And the extracellular proteins of Tgui induced systemic resistance (ISR) of maize plants to Fusarium verticillioides (Fv) (Hypocreales, Ascomycota); the ISR of maize plants may be linked to the accumulation of reactive oxygen species (ROS) and increased deposition of callose in maize tissue. Conclusions Activation of the maize immune response was triggered by the mixture of extracellular proteins secreted by Tgui into the rhizosphere. Our study thereby contributes to a better understanding of the interaction between T. guizhouense and plant roots.